Pengaruh Iklim Kerja Panas Terhadap Kelelahan Pada Pekerja Di Bagian Sizing Pt. Iskandar Indah Printing Textile Surakarta - Susanto, Agus; , dr. Hardjanto, M.S., Sp.OK; , Dr. Suwaji, M. Kes (2015)
The efficiency of the work is strongly influenced by the work climate. Temperatures that are too hot can make feeling tired and sleepy on the otherwise very cold temperatures can reduce the level of attention and calmness. It can be negatively affect on the mental work, therefore the temperature deviation either above or below the limit of comfort will give a negative impact on fatigue. The purpose of this research was to know the effect of heat work climate against in the sizing workers Pt. Iskandar Indah Printing Textile Surakarta. This research was use analitical survei methode with crossectional approaching methode. Sampling methode using purposive sampling methode as many as 30 worker that were consist of 15 sizing worker and 15 processing worker. The statistic test was using Chi Square, p value 0,025 (p<0,05) proof significan result. It can be concluded there are effect of heat work climate against in the sizing workers Pt. Iskandar Indah Printing Textile Surakarta.